Determination of minimum inhibitory concentration of cadmium salts on the microbial strains isolated from Buriganga River-bed soil - Shama, Anika Tabassum (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2019.